Design of photonic crystal based compact all-optical 2 × 1 multiplexer for optical processing devices. (June 2021) - Rao, Dalai Gowri Sankar; Swarnakar, Sandip; Kumar, Santosh
Abstract: Through this work, an all-optical 2 ​× ​1 multiplexer (MUX) is realized for optical networking and optical signal processing using two-dimensional photonic crystal waveguides. The structure consists of two T-shaped and one Y-shaped waveguide using square lattice silicon rods with a background of air. The all-optical MUX is designed without using any nonlinear material like Kerr material to overcome the problems of low gain and nonlinear susceptibility. This design works on the principle of beam-interference phenomena. The performance all-optical MUX is simulated with the help of the finite-difference-time-domain method and resultant outputs are verified using the distribution of the optical field at a wavelength of 1.55 ​μm. The proposed circuit occupies less area 7.8 ​μm ​× ​9 ​μm and provides a transmission ratio of more than 92%, a contrast ratio of 29.66 ​dB in presence of select input and 23.2 ​dB in absence of select input and it can operate with a bit rate of 1.56 Tbps.